1996
DOI: 10.1073/pnas.93.17.8940
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian dwarfins are phosphorylated in response to transforming growth factor beta and are implicated in control of cell growth.

Abstract: The dwarfin protein family has been genet- Transforming growth factor-f3 (TGF-P3) is a multifunctional polypeptide hormone that elicits a wide range of cellular effects, including inhibition of cellular proliferation and transcriptional activation of specific target genes (1, 2). The TGF-,3 signal is initiated through a heteromeric transmembrane kinase complex of type I and type II receptors (3-6). A potential mechanism of activation for the heteromeric TGF-,B receptor complex has been proposed (7). Within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 27 publications
2
86
0
Order By: Relevance
“…While these authors reported that LEF-1 and Smad3 physically interacted and synergized to activate gene expression from the Xenopus homeobox twin gene promoter, they could not detect a cooperation of both proteins on LEF/TCF-specific reporters lacking Smad-binding elements (SBE), as seen in our study. However, also other studies reported a TGFb-activated and Smad3/Smad4-induced transcriptional response independent of an SBE (Yingling et al, 1996). Thus, the different results might be due to cell-type-specific expression or activation of different sets of signalling proteins in FosER and HepG2 cells.…”
Section: Cooperation Of Lef/tcf and Smad3/4 Proteinsmentioning
confidence: 51%
“…While these authors reported that LEF-1 and Smad3 physically interacted and synergized to activate gene expression from the Xenopus homeobox twin gene promoter, they could not detect a cooperation of both proteins on LEF/TCF-specific reporters lacking Smad-binding elements (SBE), as seen in our study. However, also other studies reported a TGFb-activated and Smad3/Smad4-induced transcriptional response independent of an SBE (Yingling et al, 1996). Thus, the different results might be due to cell-type-specific expression or activation of different sets of signalling proteins in FosER and HepG2 cells.…”
Section: Cooperation Of Lef/tcf and Smad3/4 Proteinsmentioning
confidence: 51%
“…This, and the later observation that Smads have specific DNA binding activities, led to the conclusion that Smads function as transcription factors [12]. The link between activated TGF-β receptors and Smads was established with the key discovery that Smad is a substrate of the type I TGF-β receptor kinase and as a result the phosphorylated Smad concentrates in the nucleus [13][14][15]. Thus, being a signal-activated transcription factor, Smad is the central transducer of TGF-β signal.…”
Section: Introductionmentioning
confidence: 99%
“…Signaling mediators downstream of the receptors for the TGFb superfamily were recently identi®ed in a variety of organisms, and termed`Smad' in vertebrates . While seven Smad genes have been reported in the literature thus far, they can be classi®ed into three types according to their functions, i.e., receptor-activated Smads (Smad1 and Smad5 for BMP; Smad2 and Smad3 for TGF-b and activin), co-Smad (Smad4) and anti-Smads (Smad6 and Smad7) Derynck et al, 1996;Eppert et al, 1996;Gra et al, 1996;Hahn et al, 1996;Hayashi et al, 1997;Hoodless et al, 1996;Lechleider et al, 1996;Liu et al, 1996;Riggins et al, 1996;Thomsen, 1996;Topper et al, 1997;Yingling et al, 1996;Zhang et al, 1996). Smad2 and Smad3, the receptor-activated, TGFb signaling Smads, are known to be highly homologous with regard to amino acid sequence and structural characteristics, and both have been found to mediate TGF-b and activin signals by forming heteromers with Smad4 (Eppert et al, 1996;Gra et al, 1996;Riggins et al, 1996;Wrana and Pawson, 1997;Zhang et al, 1996).…”
mentioning
confidence: 99%